The Effect of Anodal Transcranial Direct Current Stimulation Over Left and Right Temporal Cortex on the Cardiovascular Response: A Comparative Study - Angius, Luca; Marcora, Samuele M.; Hopker, James G.; Mauger, Alexis R. (Frontiers in Physiology, 2018)
Background. Stimulation of the right and left anterior insular cortex, increases and decreases the cardiovascular response respectively, thus indicating the brain’s lateralisation of the neural control of circulation. Previous experiments have demonstrated that transcranial direct current stimulation (tDCS) modulates the autonomic cardiovascular control when applied over the temporal cortex. Given the importance of neural control for a normal hemodynamic response, and the potential for the use of tDCS in the treatment of cardiovascular diseases, this study investigated whether tDCS was capable of modulating autonomic regulation. Methods. Cardiovascular response was monitored during a post exercise ischemia (PEMI) test, which is well documented to increase sympathetic drive. A group of 12 healthy participants performed a PEMI test in a control (CON), sham (Sham) and two different experimental sessions where the anodal electrode was applied over the left temporal cortex (Left TC) and right temporal cortex (TC) with the cathodal electrode placed over the contralateral supraorbital area. Stimulation lasted 20 min at 2 mA. The hemodynamic profile was measured during a post-exercise muscle ischemia (PEMI) test. The cardiovascular parameters were continuously measured with a transthoracic bio-impedance device both during the PEMI test and during tDCS. Results. None of the subjects presented any side effects during or after tDCS stimulation. A consistent cardiovascular response during PEMI test was observed in all conditions. Statistical analysis did not find any significant interaction or any significant main effect of condition on cardiovascular parameters (all Ps > 0.316) after tDCS. No statistical differences regarding the hemodynamic responses were found between conditions and time during tDCS stimulation (P>0.05). Discussion. This is the first study comparing the cardiovascular response after tDCS stimulation of left and right TC both during exercise and at rest. The results of the current study suggest that anodal tDCS of the left and right TC does not affect functional cardiovascular response during exercise PEMI test and during tDCS. In light of the present and previous findings, the effect of tDCS on the cardiovascular response remains inconclusive.